Drug-induced phospholipidosis caused by combinations of common drugs in vitro - Glock, Mareike; Mühlbacher, Markus; Hurtig, Henoch; Tripal, Philipp; Kornhuber, Johannes (Toxicology in Vitro, 2016)
Drug-induced phospholipidosis (DIPLD), characterized by the accumulation of phospholipids within lysosomes, is suspected to impair lysosomal function and considered an adverse side effect of the administered medication. The increasing use of polypharmacy and the resultant elevated risks of adverse drug reactions raise the need to explore the effects of drug combinations with respect to their influence on side effects, such as DIPLD. In this study, we utilized an in vitro assay to investigate DIPLD that was caused by 24 commonly used drugs applied alone and in binary combinations with each other. Moreover, we attempted to predict the extent of DIPLD resulting from the combinations using a simple additive approach based on the increase in phospholipid levels caused by the single drugs. The results suggest that DIPLD, which was caused by combinations of drugs, occurs in an additive manner, depending on total drug concentration. Furthermore, we show that the extent of DIPLD can be predicted from the DIPLD caused by the single drugs. Thus, the simultaneous use of multiple drugs with PLD-inducing properties increases the event risk, as well as the severity of drug-induced phospholipidosis. The findings underline the importance of considering the DIPLD-inducing properties of drugs, especially in the context of polypharmacy.
EVALuna2:23782